2010 Proceedings of the 56th IEEE Holm Conference on Electrical Contacts 2010
DOI: 10.1109/holm.2010.5619518
|View full text |Cite
|
Sign up to set email alerts
|

Contact Conductance Quantization in a MEMS Switch

Abstract: When the dimensions of a metallic conductor are much smaller than the mean free path of the electrons and become comparable to the Fermi wavelength, the absence of scattering results in ballistic electron transport and the conductance becomes quantized. In this paper we present original experiments carried out in air at room temperature on MEMS switches actuated by a nanoindenter apparatus. The current and voltage curve across contact electrodes were monitored and recorded continuously while opening the switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…From an electrical contact perspective, at this point the electron transfer shifts from tunneling to direct metal-to-metal even if this nanowire is only a few atoms in diameter. There is evidence that the current carrying capability of these nanowires is extraordinarily high (on the order of 10 8 A/mm 2 ) [29][30][31]. Ψ When asperities separate, "jump out" occurs and contact continues with a thin nanowire of only a few atoms in diameter prior to breaking.…”
Section: Contact Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…From an electrical contact perspective, at this point the electron transfer shifts from tunneling to direct metal-to-metal even if this nanowire is only a few atoms in diameter. There is evidence that the current carrying capability of these nanowires is extraordinarily high (on the order of 10 8 A/mm 2 ) [29][30][31]. Ψ When asperities separate, "jump out" occurs and contact continues with a thin nanowire of only a few atoms in diameter prior to breaking.…”
Section: Contact Mechanicsmentioning
confidence: 99%
“…Theoretical analyses of Au [103], as well as Ag, Pt, and Ni [104] nanocontacts, uses molecular dynamics to show the electronics transport channels form and close during stretching and relaxation. The role of conductance quantization has been studied primarily in relation to Micro-electromechanical Systems (MEMS) switches [30], but it is noted in [29,105] that the conductance quantization is a rather general phenomenon associated to the breakage of macroscopic and microscopic contacts. As noted above, these quantum contacts have superconducting capability with current densities on the order of 10 8 A/mm 2 .…”
Section: Electrical Contactmentioning
confidence: 99%
“…Unlike Timsit, Poulain et al examined quantized conductance experimentally with micro-contacts test apparatus for breaking contact in such a way that the dimensions of the conducting members of the micro-contact were much smaller than the mean free path of an electron [32]. The team found that by using a micro-switch and a nanoindentor, they were able to witness quantized conductance plateaus before separation of the two contact members.…”
Section: Micro-contact Resistance Modelingmentioning
confidence: 99%
“…The team found that by using a micro-switch and a nanoindentor, they were able to witness quantized conductance plateaus before separation of the two contact members. The conditions for observing the quantized conduction phenomena are an extremely low switch opening speed and a current limitation near 150 μA [32]. Upper and lower micro-contacts made of Au as well as micro-contacts made of Ru-Ru were tested.…”
Section: Micro-contact Resistance Modelingmentioning
confidence: 99%
See 1 more Smart Citation